AB0684 Gender Specific Differences in Ankylosing Spondylitis at Treatment Initiation in Patients Treated with Infliximab or Golimumab. (15th July 2016) - Starr, M.; Zummer, M.; Choquette, D.; Haraoui, B.; Rahman, P.; Sheriff, M.; Rampakakis, E.; Psaradellis, E.; Osborne, B.; Lehman, A.J.; Maslova, K.; Nantel, F.; et al.
Abstract : Background: The prevalence of ankylosing spondylitis (AS) is 2–3 times higher in men compared to women. Recent studies have suggested that clinical differences exist between both genders with women experiencing a higher burden of disease. Objectives: This analysis examined gender-specific differences with respect to patient and disease parameters at initiation of infliximab (IFX) or golimumab (GLM) for the treatment of AS in a Canadian routine clinical practice setting. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis, ankylosing spondylitis, or psoriatic arthritis with IFX or GLM. Patients with AS treated with IFX who were enrolled since 2002 or with GLM enrolled since 2010 were included in this analysis. Between group differences were assessed with the Fisher's Exact test or the independent samples t-test, while linear regression was used to assess the independent association of gender with HAQ-DI, ASDAS, BASDAI, and BASFI improvements at 12 months. Results: A total of 539 AS patients were included in this analysis; 188 (34.9%) patients were treated with GLM and 351 (65.1%) with IFX. The majority of patients were male (61.8%). Mean age and disease duration were comparable between genders for both GLM and IFX, (Table 1 ). Overall, disease parameters (ESR, PtGA, MDGA, HAQ-DI, ASDAS, and BASFI) were similar for GLM with the exception of BASDAI where higher disease severity was observed among females. Among patients treated with IFX, between gender differences were observed for CRP with significantly lower levels in female patients; however BASDAI and HAQ-DI where significantly higher in females compared to males. Other parameters (ESR, PtGA, MDGA, ASDAS, and BASFI) were similar for IFX between genders. Regression analysis showed that, upon adjusting for baseline levels, female gender (ΔBASDAI=0.603; P=0.035) was associated with increased BASDAI at 12 months of treatment as compare to males. HAQ-DI, ASDAS, and BASFI, on the other hand, at 12 months were comparable between genders. Conclusions: Overall, at anti-TNF initiation, female AS patients experience greater disease activity relative to men at initiation of biologic therapy. Whether this represents a gender bias in prescribing, or a gender based difference in the acceptance of biologic treatment or disease assessment, requires additional research. Disclosure of Interest: M. Starr: None declared, M. Zummer: None declared, D. Choquette: None declared, B. Haraoui: None declared, P. Rahman: None declared, M. Sheriff: None declared, E. Rampakakis Employee of: JSS Medical Research Inc;, E. Psaradellis Employee of: JSS Medical Research Inc;, B. Osborne Employee of: Janssen, A. Lehman Employee of: Janssen, K. Maslova Employee of: Janssen, F. Nantel Employee of: Janssen, C. Tkaczyk Employee of: Janssen